GCP inspection by Roszdravnadzor - E. S. Rogov; D. Yu. Belousov; S. K. Zyryanov; A. S. Kolbin; L. I. Karpenko (Izdatelstvo OKI, 2018)
State institutions determine the rules for conducting clinical trials of drugs; therefore, they must directly monitor their conduct. The main form of control over clinical trials of drugs by the state is the inspection. This is article describes the types of inspections, the main identified violations, proposed further actions and consequences.